Clopidogrel hyper-response increases peripheral hemorrhagic complications without increasing intracranial complications in endovascular aneurysm treatments requiring dual antiplatelet therapy. (November 2022) - Young, Christopher C.; Bass, David I.; Cruz, Michael J.; Carroll, Kate; Vanent, Kevin N.; Lee, Chungeun; Sen, Rajeev D.; Feroze, Abdullah H.; Williams, John R.; Levy, Samuel; McCray, Denzel; Kelly, Cory M.; et al.
Highlights: Hemorrhage and thrombosis are of concern in neuroendovascular procedures. Clopidogrel and aspirin are used to prevent thromboembolic complications. Therapeutic and increased clopidogrel response show similar intracranial complication rate. Clopidogrel hypo-response can be successfully mitigated once identified. Preoperative VNP assays help guide DAPT management in endovascular aneurysm treatment. Abstract: Clinical significance of increased clopidogrel response measured by VerifyNow P2Y12 assay is unclear; management guidelines are lacking in the context of neuroendovascular intervention. Our objective was to assess whether increased clopidogrel response predicts complications from endovascular aneurysm treatment requiring dual antiplatelet therapy. A single-institution, 9-year retrospective study of patients undergoing endovascular treatments for ruptured and unruptured aneurysms requiring aspirin and clopidogrel was conducted. Patients were grouped according to preoperative platelet inhibition in response to clopidogrel measured by the VerifyNow P2Y12 assay (VNP; P2Y12 reactivity units, PRU). Demographic and clinical features were compared across groups. Hemorrhagic complication rates (intracranial, major extracranial, minor extracranial) and thromboembolic complications (in-stent stenosis, stroke/transient ischemic attack) were compared, controlling for potential confounders and multiple comparisons. Data were collected from 284 patients across 317 procedures. Pre-operative VNP assays identified 9 % Extreme Responders (PRU ≤ 15), 13 % Hyper-Responders (PRU 16–60), 62 % Therapeutic Responders (PRU 61–214), 16 % Hypo-Responders (PRU ≥ 215). Increased response to clopidogrel was associated with increased risk of any hemorrhagic complication (≤60 PRU vs > 60 PRU; 39 % vs 24 %, P = 0.050); all intracranial hemorrhages occurred in patients with PRU > 60. Thromboembolic complications were similar between therapeutic and subtherapeutic patients (<215 PRU vs ≥ 215 PRU; 15 % vs 16 %, P = 0.835). Increased preoperative clopidogrel response is associated with increased rate of extracranial hemorrhagic complications in endovascular aneurysm treatments. Hyper-responders (16–60 PRU) and Extreme Responders (≤15 PRU) were not associated with intracranial hemorrhagic or thrombotic complications. Hypo-responders who underwent adjustment of antiplatelet therapy and neurointerventions did not experience higher rates of complications.